Pendampingan UMKM Mengurus Sertifikat Produk Halal Se-Labuhanbatu Raya - Iwan Purnama; Elysa Rohayani Hasibuan; Puput Indrayani; Raja Inganta Sinulingga; Safaridah Rambe (Jurnal Pengabdian Masyarakat Gemilang (JPMG), 2023)
The purpose of this study is to find out assistance in obtaining halal certificates for UMKM in se-Labuhantau Raya. In this study, service team used qualitative research methods. The types of data in this study were primary data and secondary data. Primary data were obtained by the service team through interviews with mentors in an effort to collect data in this study, namely through interviews and using documentation by seeking information and references in the form of journals and information from the internet. Halal certification plays an important role in ensuring that the businesses produced by UMKM actors are free from illicit products ranging from raw materials, production processes to the product halal assurance system that meets the standards of LPPOM MUI. The training and mentoring for UMKM in Labuhanbatu Raya was carried out through socialization and mentoring of NIB and assistance with halal labels. The total halal certificates that will be assisted through community service are 151 Halal Certificates with a distribution of 104 certificates in Labuhanbatu, 27 certificates in South Labuhanbatu and 19 certificates in North Labuhanbatu. This assistance effort is able to make UMKM actors aware of the importance of halal labels and be able to educate UMKM actors se-Labuhanbatu Raya in maintaining the quality of their products so that in this rapidly growing era the products that have been produced are able to compete with other products.